Age and sex-specific stroke epidemiology in COVID-19 - Kim, Youngran; Parekh, Maria A.; Li, Xiaojin; Huang, Yan; Zhang, Guo-Qiang; Manwani, Bharti (Frontiers in Stroke, 2023)
Background COVID-19 has emerged as an independent risk factor for stroke. We aimed to determine age and sex-specific stroke incidence and risk factors with COVID-19 in the US using a large electronic health record (EHR) that included both inpatients and outpatients. Methods A retrospective cohort study was conducted using individual-level data from Optum® de-identified COVID-19 EHR. A total of 387,330 individuals aged ≥ 18 with laboratory-confirmed COVID-19 between March 1, 2020 and December 31, 2020 were included. The primary outcome was cumulative incidence of stroke after COVID-19 confirmation within 180 days of follow-up or until death. Kaplan–Meier cumulative incidence curves for acute ischemic stroke (AIS), intracerebral hemorrhage (ICH), and a composite outcome of all strokes were stratified by sex and age, and the differences in curves were assessed using a log-rank test. The relative risk of stroke by demographics and risk factors was estimated using multivariable Cox-proportional hazards regressions and adjusted hazard ratios (aHRs). Results Of 387,330 COVID-19 patients, 2,752 patients (0.71%, 95% CI 0.68–0.74) developed stroke during the 180-day follow-up, AIS in 0.65% (95% CI 0.62–0.67), and ICH in 0.11% (95% CI 0.10–0.12). Of strokes among COVID-19 patients, 57% occurred within 3 days. Advanced age was associated with a substantially higher stroke risk, with aHR 6.92 (5.72–8.38) for ages 65–74, 9.42 (7.74–11.47) for ages 75–84, and 11.35 (9.20–14.00) for ages 85 and older compared to ages 18–44 years. Men had a 32% higher risk of stroke compared to women. African-American [aHR 1.78 (1.61–1.97)] and Hispanic patients [aHR 1.48 (1.30–1.69)] with COVID-19 had an increased risk of stroke compared to white patients. Conclusion This study has several important findings. AIS and ICH risk in patients with COVID-19 is highest in the first 3 days of COVID-19 positivity; this risk decreases with time. The incidence of stroke in patients with COVID-19 (both inpatient and outpatient) is 0.65% for AIS and 0.11% for ICH during the 180-day follow-up. Traditional stroke risk factors increase the risk of stroke in patients with COVID-19. Male sex is an independent risk factor for stroke in COVID-19 patients across all age groups. African-American and Hispanic patients have a higher risk of stroke from COVID-19.